2009
DOI: 10.1007/s11095-009-9908-0
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan/TPP and Chitosan/TPP-hyaluronic Acid Nanoparticles: Systematic Optimisation of the Preparative Process and Preliminary Biological Evaluation

Abstract: Three optimised nanoparticles have been developed (two uncoated and one HA-coated) and their toxicity on fibroblasts and macrophages has been evaluated: experiments showed the beneficial character of HA-coating in the reduction of toxicity (IC50 raised from 0.7-0.8 mg/mL to 1.8 mg/mL) and suggested that the uncoated chitosan/TPP nanoparticles had toxic effects following internalisation rather than membrane disruption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
188
2
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 281 publications
(202 citation statements)
references
References 54 publications
(52 reference statements)
9
188
2
3
Order By: Relevance
“…24,25 The CS/TPP-HA NPs have been recently proven to be a powerful vehicle for gene delivery, even to the spinal cord. 21,26 In our study, the NPs also showed significant knockdown efficiency. The TPP-HA is negatively charged, which could facilitate the NPs formation with positively charged …”
Section: Discussionsupporting
confidence: 67%
“…24,25 The CS/TPP-HA NPs have been recently proven to be a powerful vehicle for gene delivery, even to the spinal cord. 21,26 In our study, the NPs also showed significant knockdown efficiency. The TPP-HA is negatively charged, which could facilitate the NPs formation with positively charged …”
Section: Discussionsupporting
confidence: 67%
“…Additionally, the concentration of both CMC-COS NP and SC-COS NP that induced optimal cell proliferation was 50 mg/mL (p 5 0.05), but not 100 mg/mL. This result implies that an excessive amount of chitosan-based nanoparticles may have an unfavourable effect on cells, which was similar to the previously reported reduction in fibroblasts proliferation that was observed following application of chitosan-tripolyphosphate nanoparticles [21].…”
Section: Effect Of Cmc-cos Np and Sc-cos Np On 3t6 Mouse Fibroblasts supporting
confidence: 77%
“…30,31 The adjustment of parameters such as CS concentration, the CS:TPP polymer ratio, and mixing conditions control CS-TPP NP size. [32][33][34] Initial studies aiming to optimize NP formation were conducted. Particle size and particle size and polydispersity were measured with a Zetasizer Nano.…”
Section: Preparation Of Cs-tpp Npsmentioning
confidence: 99%